The Value of Consulting Services for Achieving High Levels of Performance within European Funded Projects - Madalin DARIE; Alexandru CAPATINA; George Cristian SCHIN; Angela-Eliza MICU; Adrian MICU (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2023)
Consulting services play a crucial role in enhancing the performance of European funded projects. These projects often require specialized knowledge, multidisciplinary skills, and adherence to complex guidelines. This paper attempts to explore the role of consulting services in achieving the expected levels of performance in the case of EU funded projects. The correlations among five latent variables (the level of knowledge of the consulting team, the level of involvement of the consulting team, effective communication with project beneficiaries, confidence in the quality of consulting services and the performance within the projects with European funding) are analyzed using a structural model. The findings reveal interesting insights related to the interplay between the enablers of successful EU projects’ implementation. Consulting firms offer project management tools and expertise to ensure projects are executed in line with EU guidelines.